2021
DOI: 10.3390/ijms222212308
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Calcium Signaling and Transport in Plant Adaptation to Abiotic Stress

Abstract: Adaptation to unfavorable abiotic stresses is one of the key processes in the evolution of plants. Calcium (Ca2+) signaling is characterized by the spatiotemporal pattern of Ca2+ distribution and the activities of multi-domain proteins in integrating environmental stimuli and cellular responses, which are crucial early events in abiotic stress responses in plants. However, a comprehensive summary and explanation for evolutionary and functional synergies in Ca2+ signaling remains elusive in green plants. We rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 173 publications
2
15
0
1
Order By: Relevance
“…Altogether, our results show a highly diverse and dynamic pattern regarding the expression of calcium transporters (Ca-channel, Ca-ATPase), which seems to be related to the species, but based on the intraspecific comparison of Phymatolithon sp., can also be modulated by the environment (Figure 8). It agrees with the reported high variability in the presence/absence of gene sequences associated to calcium transporters, such as Ca-ATPase and Ca 2+ /H + exchangers in Rhodophyta (Schönknecht, 2013;Tong et al, 2021).…”
Section: Rhodolith Calcification Mechanismsupporting
confidence: 91%
“…Altogether, our results show a highly diverse and dynamic pattern regarding the expression of calcium transporters (Ca-channel, Ca-ATPase), which seems to be related to the species, but based on the intraspecific comparison of Phymatolithon sp., can also be modulated by the environment (Figure 8). It agrees with the reported high variability in the presence/absence of gene sequences associated to calcium transporters, such as Ca-ATPase and Ca 2+ /H + exchangers in Rhodophyta (Schönknecht, 2013;Tong et al, 2021).…”
Section: Rhodolith Calcification Mechanismsupporting
confidence: 91%
“…The overall trend in the evolutionary process of green plants is a significant and sustained increase in the number of EF-hand domains, whereas the number of EFhands was initially very low in early algae, indicating that Ca 2+ sensing appeared to experience differential expansion and functional specialization in CDPKs, CMLs, CaMs, and CBLs. Abiotic stresses and plant morphological complexity may also be linked to changes in the number of Ca 2+ -sensing genes and EFhand motifs (Tong et al, 2021). Considering the evolutionary history of CDPKs it is established that, this multigene family is conserved among angiosperms based on their basal architecture and gene structure which has contributed to expanding their signaling roles.…”
Section: Evolutionary Pattern and Functional Changes In The Cdpk Fami...mentioning
confidence: 99%
“…Thus, the evolutionary histories of redox homeostasis and photosynthesis can be drawn through comparative genetic analysis, gene expression profiles, phylogenies, conserved domain analysis, and prediction of 3D protein structures. In our previous comparative molecular evolution studies, we have revealed conserved features of over 100 gene families in green algae and land plants [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Here, the functional regulatory networks among distinct species were analyzed through comparative genetic analysis of sequences in redox signaling of photosynthesis from evolutionarily important lineages of plants and algae ( Figure 2 and Figure 3 , Supplementary Figures S2–S5 ).…”
Section: Molecular Evolution Of Redox Regulatory Networkmentioning
confidence: 99%